Evaluation of a Targeted Drug‐Eluting Intravascular Nanotherapy to Prevent Neointimal Hyperplasia in an Atherosclerotic Rat Model. Issue 7 (3rd May 2021) - Newton, Emily R.; Gillis, David C.; Sun, Kui; Dandurand, Brooke R.; Siletzky, Robin; Biswas, Suvendu; Karver, Mark R.; Tsihlis, Nick D.; Stupp, Samuel I.; Kibbe, Melina R.
Abstract : Herein the hypothesis that nitric oxide–bearing collagen‐targeted nanofibers will target vascular injury and inhibit neointimal hyperplasia in an atherosclerotic rat model is tested. Western blot confirms the apolipoprotein E (ApoE) knockout (‐/‐) status. Serum cholesterol increases threefold in Sprague Dawley (SD) ApoE‐/‐ versus wt SD rats (291.7 ± 22.3 vs 105.0 ± 3.6 mg dL −1, p < 0.05). Oxidative stress markers are elevated in SD ApoE‐/‐ vs wt SD strains ( p = 0.002). Oil Red O staining shows lipid‐rich lesions in SD ApoE‐/‐ aortas. Transmission electron microscopy shows coassembled peptide amphiphiles (PA) form nanofibers. Fluorescence microscopy shows targeting of collagen‐binding peptide (CBP)‐S‐nitrosyl (SNO)‐PA nanofiber to arteries 20 min after injury, whereas uninjured carotid and nontargeted SNO‐PA nanofibers show minimal localization (3444.8 ± 282.0, 11.0 ± 2.3, and 451.4 ± 93.6 arbitrary units, respectively, p < 0.05). Two weeks after injury and injection, CBP‐SNO‐PA nanofibers inhibit neointimal hyperplasia by 67% versus injury alone ( p < 0.0001). Intima/media (I/M) ratios are 0.3, 1.0, and 0.9 for CBP‐SNO‐PA nanofiber, scrambled SNO‐PA nanofiber, and injury alone, respectively ( p < 0.0001). Results are durable out to 3 months (I/M 0.6 vs 1.4 for CBP‐SNO‐PA vs injury alone, p < 0.0001). Targeted drug‐eluting nanofibers localize to vascular injury, decrease neointimal hyperplasia after 2 weeks, and are durable out to 3 months in an atherosclerotic rat model. Abstract : Herein, a collagen‐targeted nitric‐oxide‐bearing nanofiber is assessed to an atherosclerotic model, Sprague Dawley ApoE‐/‐ rats. Higher cholesterol, oxidative stress, and development of atherosclerosis are observed in ApoE‐/‐ rats. Despite these changes, the nanotherapy localizes to injury with minimal off‐target localization, and decreases restenosis by 67% 2 weeks after injury, an effect that is durable up to 3 months.